Analysis of DEM interpolation accuracy based on radial basis kernel function in different topographic conditions - Liu, Xiaonan; Zhang, Hengjing (Proceedings of SPIE, the international society for optical engineering, 2025)
In order to solve the problem of the applicability of the interpolation accuracy of different kernel functions under different terrain conditions, the radial basis multi-kernel function algorithm (RBF) is taken as the research object of four different geomorphological terrains: mountains, plains, urban areas and mountains Spatial interpolation and evaluation of the interpolation accuracy of different kernel functions in a variety of terrains. The experimental results show that: 1. In the plain terrain, the interpolation of the cubic kernel function is the best; mountains, urban areas and mountains performed better in the quintic kernel function. 2. When the kernel function is fixed, the more average the elevation point data (the value range is small and the dispersion is small), the higher the interpolation accuracy. vice versa; 3. Generate DEM comprehensive analysis, the quintic kernel function has the best interpolation effect in urban areas, mountains, and mountains, while the cubic kernel function is more suitable for plains.